Molecular epidemiology and evolutionary trajectory of emerging echovirus 30, Europe - Benschop, KSM; Broberg, EK; Hodcroft, E; Schmitz, D; Albert, J; Baicus, A; Bailly, J-L; Baldvinsdottir, G; Berginc, N; Blomqvist, S; Böttcher, S; Brytting, M; et al. (Centers for Disease Control and Prevention, 2021)
In 2018, an upsurge in echovirus 30 (E30) infections was reported in Europe. We conducted a large-scale epidemiologic and evolutionary study of 1,329 E30 strains collected in 22 countries in Europe during 2016–2018. Most E30 cases affected persons 0–4 years of age (29%) and 25–34 years of age (27%). Sequences were divided into 6 genetic clades (G1–G6). Most (53%) sequences belonged to G1, followed by G6 (23%), G2 (17%), G4 (4%), G3 (0.3%), and G5 (0.2%). Each clade encompassed unique individual recombinant forms; G1 and G4 displayed >2 unique recombinant forms. Rapid turnover of new clades and recombinant forms occurred over time. Clades G1 and G6 dominated in 2018, suggesting the E30 upsurge was caused by emergence of 2 distinct clades circulating in Europe. Investigation into the mechanisms behind the rapid turnover of E30 is crucial for clarifying the epidemiology and evolution of these enterovirus infections.